2019
DOI: 10.1039/c9ta00682f
|View full text |Cite
|
Sign up to set email alerts
|

A flexible active dual-parameter sensor for sensitive temperature and physiological signal monitoring via integrating thermoelectric and piezoelectric conversion

Abstract: A flexible active dual-parameter sensor for sensitive temperature and physiological signal monitoring has been developed via integrating thermoelectric and piezoelectric conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 42 publications
0
58
0
Order By: Relevance
“…For example, a flexible thermoelectric module can be assembled when thermoelectric legs are combined with flexible Cu electrodes and stretchable sheets (Figure 2d,e) [30][31][32][33] Other novel practical applications can also be boosted by the development of highly flexible thermoelectric materials. For example, Zhu et al [34] integrated thermoelectric and piezoelectric materials to form a flexible active dual-parameter sensor for monitoring a range of physiological signals along with temperature ( Figure 2f). Moreover, the improved flexibility of thermoelectric materials and generators can promote their application in electrocardiographic systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a flexible thermoelectric module can be assembled when thermoelectric legs are combined with flexible Cu electrodes and stretchable sheets (Figure 2d,e) [30][31][32][33] Other novel practical applications can also be boosted by the development of highly flexible thermoelectric materials. For example, Zhu et al [34] integrated thermoelectric and piezoelectric materials to form a flexible active dual-parameter sensor for monitoring a range of physiological signals along with temperature ( Figure 2f). Moreover, the improved flexibility of thermoelectric materials and generators can promote their application in electrocardiographic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Energy harvesting technologies have received rapid development in the past decade, including the widely adopted piezoelectric, electromagnetic, electrostatic, triboelectric, thermoelectric, pyroelectric, photovoltaic transducing mechanisms, and so on. In the field of flexible wearable electronics, thermoelectric, 213 piezoelectric, 214‐216 triboelectric, 217‐219 photovoltaic, 220 and their hybrid mechanisms 221 are commonly adopted due to the good compatibility. Briefly speaking, thermoelectric energy harvesters/generators are based on the Seebeck effect of thermoelectric materials to generate electricity under an existing temperature gradient, such as that between the human body and the ambient environment.…”
Section: Self‐sustainable Wearable Electronics Integrated With Energymentioning
confidence: 99%
“…Sensors. NGs could also be applied for motion monitoring [119,133,134]. Zou et al reported a bionic stretchable and flexible NG with a structure of ion channels for underwater energy harvesting and human motion monitoring as shown in Figure 6(c) [135].…”
Section: Motionmentioning
confidence: 99%
“…A flexible and textile TENG for energy harvesting has proved the possibility as a strain sensor for strain sensing [109]. The integrated device was prepared in a single silk chip and could be adhered to the skin or fabrics to collect the biomechanical energy and detect strain at Position/accessory Finger [124][125][126]128] Finger skin [127] Finger and hand [129] Hand [131,132] Wrist [130] Hand and chest [119] Sock [133] Elbow and wrist [134] Arm and leg [135] Wrist, foot, elbow, knee [137] Cap or jaw [138] Joint [106] Forearm, shirt, pants [109] Abdomen [117] Thumb and wrist [140] Finger [141,144] Cotton glove [142] Finger, elbow, arm, knee [143] Elbow, leg, neck [106] Respirator [108,145,148] Finger [107] Waist and abdomen [116] Hand and fingertip [147] Flexibility Yes [124][125][126][127][128][129][130][131][132] Yes [133][134][135]…”
Section: Strain Sensorsmentioning
confidence: 99%